Mindfulness and Its Pedagogical Application in Business Education - Chulguen (Charlie) Yang; Goralski, Margaret A. (Journal of International Business Disciplines, 2016)
Mindfulness has gained significant attention and momentum in business and popular culture in the US, Europe, and Australia. There is, however, a paucity of literature on how business students make sense of mindfulness and its practices. Based on our experiences of adopting mindfulness and mindfulness meditation in our teachings of management courses, we have explored how business students make sense of mindfulness and meditation. From a phenomenological perspective, we have examined our students' meditation journals, essays, and their own research on the topic of mindfulness. Based on the findings of previous empirical studies on the positive effects of mindfulness practices and our reflections on the pedagogical potential of mindfulness meditation for business education, we have emphasized that the practice of presence through mindfulness tends to enhance the business students' self-awareness and emotional skills. The implications of adopting mindfulness research and brief and deliberate practices into the business curriculum to develop embodied wisdom are also discussed.
Keywords: BUSINESS education; BUSINESS students; MANAGEMENT; MEDITATION; MINDFULNESS; POPULAR culture; UNITED States; dept.mgt; peer-reviewed